A two degrees of freedom system for wheel traction applications - Roggia, Sara; Cupertino, Francesco; Gerada, Chris; Galea, Michael (Institute of Electrical and Electronics Engineers, 2018)
In this paper, the use of conical induction machines is proposed for an in-wheel traction application. Such machines offer a rotational movement combined with a translational motion of the rotor. The horizontal movement is essential when active engagement and disengagement of the motor from the wheel without any extra mechanical component is required. This paper first investigates the basic concepts of how the conical machine functions and then proposes a mission strategy for a relevant traction application. A detailed description of the full scheme is given. In order to achieve the required performance, an innovative control method for both degrees of freedom of the machine (i.e. torque production and axial movement) is proposed and validated against a small-scale demonstrator of the whole system.